Analisis Perencanaan Desain Jaringan Distribusi Air Bersih Pada Proyek CWP-01 Pembangunan Gedung Fakultas Pendidikan Teknologi dan Kejuruan - Mochamad Permana Sidik; Sri Rahayu; Hery Wiharja (Akademi Komunitas Negeri Aceh Barat, 2022)
AbstractThe clean water distribution system is one of the most important things in a building. Especially in the construction of the Faculty of Technology and Vocational Education building which functions as a means of educational services, a good clean water distribution system must be needed in order to get smooth learning. The purpose of this study was to determine the need for clean water, ground water tanks and roof tanks, pipe diameters, and clean water pumps in the FPTK building. The data collection technique was carried out with the first stages of observation in the form of observations of the clean water distribution system, then interviews in the form of questions and answers with PT.Ciriajasa Cipta Mandiri as a project consultant, then the last one was a study of documentation in the form of specifications image data and work plans requirements. Based on the results of the calculation analysis, it is known that to meet the need for clean water with a population of 592 people, 56.83 m3/day of clean water is needed, then the ground water tank and roof tank volumes can be designed at 18.944 m3/hour and 0.473 m3/hour. With the required pipe diameter using 2 inch, 1 inch, 1 inch, 1 inch. To meet the need for clean water, a pump with a head of 59.32 m is required and the pump specifications are obtained, namely with a suction diameter of 50 mm, an exhaust diameter of 40 mm, a number of valves 2, a frequency of 50 Hz and a motor power of 5.5 kW. Keywords:Clean Water Distribution; Water Needs; Pipe; Pump.__________________________ AbstrakSistem distribusi air bersih merupakan salah satu hal yang sangat penting pada suatu gedung. Terutama dalam pembangunan gedung Fakultas Pendidikan Teknologi dan Kejuruan yang berfungsi sebagai sarana pelayanan pendidikan, harus dibutuhkan sistem distribusi air bersih yang baik agar mendapatkan kelancaran dalam pembelajaran. Tujuan Penelitian ini untuk mengetahui kebutuhan air bersih, ground water tank dan rooftank, diameter pipa, dan pompa air bersih pada gedung FPTK. Teknik pengumpulan data dilakukan dengan tahapan yang pertama observasi berupa pengamatan mengenai sistem distribusi air bersih , kemudian wawancara berupa tanya jawab dengan PT.Ciriajasa Cipta Mandiri sebagai konsultan proyek, kemudian yang terakhir studi dokumentasi berupa data gambar bestek dan rencana kerja syarat. Berdasarkan hasil analisis perhitungan diketahui bahwa untuk memenuhi kebutuhan air bersih dengan jumlah penghuni 592 orang diperlukan air bersih sebesar 56,83 m3/hari, kemudian dapat dirancang volume ground water tank dan rooftank sebesar 18,944 m3/jam dan 0,473 m3/jam. Dengan diameter pipa yang diperlukan menggunakan 2 inch, 1 inch, 1 ½ inch, 1 ¼ inch . Untuk memenuhi kebutuhan air bersih diperlukan pompa dengan head 59,32 m dan didapat spesifikasi pompa yaitu dengan diameter isap 50 mm, diameter buang 40 mm, jumlah katub 2, frekuensi 50 Hz dan daya motor 5,5 kW. Kata Kunci:Pendistribusian Air Bersih; Kebutuhan air; Pipa; Pompa.